Narcissism Of Hijabi Women Among Students On The Tiktok Application - Maretha, Atsilah Aulia; Octaviani , Vethy; Risdiyanto, Bayu (Social Sciences Journal, 2024)
Advances in information and communication technology have opened a new stage for people to obtain information autonomously. This research aims to determine the narcissism of women wearing the hijab among students on the Dehasen Bengkulu University TikTok application. This research uses Santrock's theory of narcissism with qualitative research methods. The subjects of this research consisted of 3 informants from the 2020 and 2023 Communication Science Study Program at Dehasen University. Data collection techniques were carried out using observation, interviews and documentation. From the results of the author's observations, it can be seen that the form of narcissism found in women who wear the hijab is those who love themselves without caring about other people's opinions about themselves, who make trending videos on the TikTok application using the hijab, and often use excessive filters. Such as using lipstick filters, false eyelashes and bleach on their faces to make them look more beautiful and show off their strengths. When live, they also show body language and body shape while swaying and wearing tight clothes while wearing the hijab. It is better for women who wear the hijab not to do this. However, the informant considered this appearance to be a simple thing, because according to the informant, wearing the hijab was an obligation, while creating trends on the TikTok application was just self-indulgence and entertainment.